PENGARUH PEMBERIAN AROMATERAPI LAVENDER TERHADAP PERUBAHAN KUALITAS TIDUR MAHASISWA KEPERAWATAN SEMESTER AKHIR - Rahmah, Norhaliza; Kausar, Lola Illona Elfani; Rachmawati, Kurnia (Universitas Islam Negeri Alauddin Makassar, 2025)
Background: The phenomenon experienced by final semester nursing students often experiences poor sleep quality due to physical fatigue, stress and delaying sleep to complete the thesis. These sleep problems will have an impact on emotional intelligence and student activities such as memory and learning concentration. Nursing interventions that can be used in non-pharmacological sleep disorders are lavender aromatherapy with a calming effect on the physical and can improve sleep quality.Objectives: Knowing the effect of giving lavender aromatherapy on changes in the quality of sleep of nursing students in the final semester of Universitas Lambung Mangkurat. Method: This study used quasi experimental with pre test and post test approach with control group. The population of this study was 73 nursing students, a sample of 34 respondents, 17 respondents each for the treatment and control groups using the Wilcoxon Signed Rank Test and the Mann-Whitney U test.Results: The effect of lavender aromatherapy on changes in sleep quality of final semester nursing students with a value (p-Value = 0.001 <0.05). Discussion: Giving lavender aromatherapy can have a relax effect on the body, mind, feelings, stress and anxiety when wanting to sleep so that it can fixing one's sleep quality.